PREVALENCE OF OBESITY AMONG THE SCHOOL-GOING CHILDREN OF LAHORE AND ASSOCIATED FACTORS - Anwar, Adeel; Anwar, Faisal; Joiya, Habib Ullah; Ijaz, Azhar; Rashid, Haroon; Javaid, Atif; Mehmood, Moazam (Journal of Ayub Medical College Abbottabad, 2010)
Objective: To determine the prevalence of obesity among the school- going children (6th and 7th grade) of Lahore and ascertain the associated factors. Method: A descriptive study with sample size of 293 children conducted over a period of four months in two private sector schools of Lahore. Information was gathered by the help of a pre designed questionnaire after getting formal consent from parents. Children included in the study were healthy with no reported chronic illness. Body weight was measured in minimal clothing using a weight scale; body height was measured in erect posture without shoes using a stadiometer. Obesity, underweight and overweight were defined by plotting BMI against age (in months and years) on WHO BMI-for-age (5-19 years [percentiles]) charts. Results: Out of 293 children 11.9% were obese (more than 97th percentile) while 21.8% were overweight (85th-97th percentile). Among obese children 74.3% were found to watch TV for 1-2 hours daily while 25.7% watch TV for 3-4 hours. 48.6% of obese children did not participate in any field sports while 34.3% have less than 3 hours participation in field sports. Among parents of obese children, 60% were found to have little or no influence on their children's food intake at school whereas 22.9% parents of obese children never advise them against eating junk food. Parents think that ban on advertisements promoting unhealthy foods (75.1%) and use of popular media characters in promoting healthy foods (83.6%) and exercise can help in preventing obesity in children. Conclusion: This study shows that high prevalence of obesity and overweight among children in private schools has direct relationship with decreased physical activity and other factors like watching TV, role of media and lack of diet control by parents. Keywords: obesity, children, school age, parents, physical activity